Inter-laboratory study on electrochemical methods for the characterization of CoCrMo biomedical alloys in simulated body fluids - Mischler, S.; Igual Munoz, A. (Maney Pub., 2011)
Annotation All metals and alloys are subject to corrosion when in contact with body fluid due to the presence of chloride ions and oxygen. Although the extent of corrosion is low because of the passive surface films usually present on surgical implants it has clinical consequences and there is a need for a better understanding of the process. An inter-laboratory study involving 15 laboratories from Europe and Japan has been undertaken under the auspices of the European Cooperation on Science and Technology (COST) 533 Project: Materials for Improved Wear Resistance of Total Artificial Joints. The aim of this work, which is being conducted with the support of EFC Working Party 18 on Tribocorrosion, is to evaluate the reproducibility of the electrochemical test methods currently used to study the corrosion of biomaterials. A 65 % Co, 28 % Cr, 6 % Mo alloy was used for the collaborative investigation. Generally good qualitative agreement was obtained between the various participants. However, an important outcome of the study was that the present scientific understanding of CoCrMo corrosion is not sufficient to design electrochemical experiments for the reliable quantitative determination of corrosion rates in biological fluids. This important outcome highlights the need for improved electrochemical test methods, especially with regard to surface preparation, chemical and electrochemical pre-conditioning, solution aeration and data extraction. The book will be of great interest to everyone involved in the determination of potentiodynamic polarisation curves and electrochemical impedance spectra. Chapters include: Introduction and rationale; Electrochemical corrosion study of biomedical alloys; Protocol for the inter-laboratory study ; Results; Discussion; Conclusion.
"Published for the European Federation of Corrosion by Maney Publishing on behalf of The Institute of Materials, Minerals & Mining."
Title page uses the British spelling of "characterisation."
Keywords: Orthopedic implants -- Materials -- Corrosion.; Orthopedic implants.; Body fluids.; Corrosion and anti-corrosives.; elektronické knihy; electronic books